Print Culture, Crime and Justice in 18th-Century London - Ward, Richard M. (History of Crime, Deviance and Punishment, 2014)
In the first half of the 18th century there was an explosion in the volume and variety of crime literature published in London. This was a 'golden age of writing about crime', when the older genres of criminal biographies, social policy pamphlets and 'last-dying speeches' were joined by a raft of new publications, including newspapers, periodicals, graphic prints, the Old Bailey Proceedings and the Ordinary's Account of malefactors executed at Tyburn. By the early 18th century propertied Londoners read a wider array of printed texts and images about criminal offenders - highwaymen, housebreake